“Placement Budgets” for Supported Employment—Impact on Quality of Life in a Multicenter Randomized Controlled Trial - Rössler, Wulf; Kawohl, Wolfram; Nordt, Carlos; Haker, Helene; Rüsch, Nicolas; Hengartner, Michael P. (Frontiers in Psychiatry, 2018)
Background: Employment is an important aspect of psychiatric rehabilitation. The objective of this analysis was to explore how quality of life (QoL) may affect the outcome of supported employment and vice versa. Methods: A total of 116 participants with severe mental disorders were randomly assigned to either 25h, 40h or 55h placement budgets, which comprises job coaches’ time resources to support a client in finding a job. The intervention followed the individual placement and support model and lasted up to 36 months. Primary outcome was employment in the first labour market for at least three months. QoL was assessed 7 times over the entire 36-month observation period using the WHO QoL Bref, which comprises the dimensions physical health, psychological, social relationships, and environment. Results: The three placement budgets did not differentially relate to QoL, but QoL environment showed a significant increase over time across all three groups. Baseline QoL environment weakly predicted subsequent obtainment of employment (F=4.08, df=1, p=0.046, Cohen’s d=0.39). Controlling for baseline QoL, those participants who obtained a job, as compared to those who did not, showed persistent increases in QoL physical health (b=0.39, p=0.002, Cohen’s d=0.50) and QoL psychological (b=0.40, p<0.001, Cohen’s d=0.47). Conclusion: Obtaining employment in the first labour market improves patients’ QoL. Supported employment is a valuable intervention that may benefit patients with severe mental disorder.